The Effect of Simvastatin on Acute Phase Functional Outcome of Ischemic Stroke - Fidiana Fidiana; Paulus Sugianto (AKSONA, 2022)
Introduction: Stroke is one of the leading causes of death and disability worldwide, and especially in Indonesia. Several studies showed the pleiotropic and neuroprotective effect of simvastatin in addition to lowering blood cholesterol levels. Objective: This trial was conducted to investigate if the administration of simvastatin in acute ischemic stroke management can improve functional outcomes. Methods: This randomized, double-blind, placebo-controlled trial of simvastatin was conducted in patients with acute ischemic stroke with an NIHSS score of 4-14. Participants were randomly assigned to receive 40 mg of simvastatin or placebo for seven days. The NIHSS scale was compared on admission day, 4th and 8th day after administration of simvastatin between the two groups. Results: 52 individuals were randomized: 28 to simvastatin and 24 to placebo. There was no significant improvement of functional outcome between the two groups (p > 0.05). Conclusion: Administration of simvastatin had no significant effect on outcome (measured by NIHSS) in patients with acute ischemic stroke.